Picturing Cuba : Art, Culture, and Identity on the Island and in the Diaspora - Duany, Jorge (Book collections on Project MUSE., 2019)
Picturing Cuba explores the evolution of Cuban visual art and its links to cubanía, or Cuban cultural identity. Featuring artwork from the Spanish colonial, republican, and postrevolutionary periods of Cuban history, as well as the contemporary diaspora, these richly illustrated essays trace the creation of Cuban art through shifting political, social, and cultural circumstances. Contributors examine colonial-era lithographs of Cuba's landscape, architecture, people, and customs that portrayed the island as an exotic, tropical location. They show how the avant-garde painters of the vanguardia, or Havana School, wrestled with the significance of the island's African and indigenous roots, and they also highlight subversive photography that depicts the harsh realities of life after the Cuban Revolution. They explore art created by the first generation of postrevolutionary exiles, which reflects a new identity--lo cubanoamericano, Cuban-Americanness--and expresses the sense of displacement experienced by Cubans who resettled in another country. A concluding chapter evaluates contemporary attitudes toward collecting and exhibiting post-revolutionary Cuban art in the United States. Encompassing works by Cubans on the island, in exile, and born in America, this volume delves into defining moments in Cuban art across three centuries, offering a kaleidoscopic view of the island's people, culture, and history.